Agricultural Drought Monitoring Using Climatic, Vegetation and Soil Moisture Data in Hormozgan Province - Mohsen Nouro Pourdargazi; Ommolbanin Bazrafshan; Yahya Esmaelpour (Nīvār)
The current study deals with the monitoring and evaluation of soil moisture and vegetation changes using remote sensing technique and its relationship with the standardized precipitation-evapotranspiration index in Bandar-Dij and Kol-Mehran watersheds in Hormozgan province. For this purpose, soil moisture data at a depth of 0-10 cm was calculated from GLDAS satellite images and standardized soil moisture drought index (SMDI) and standardized normalized difference vegetation index (SNDVI) were used to calculate changes in vegetation cover. The results of the correlation between SPEI and Standardized Moisture Drought Index (SMDI) showed that in all sub-basins, the correlation coefficients increase with the increase of the time scale, and the highest correlation is related to the Minab sub-basin (R=0.764) in the 12-month time scale. Examining the characteristics of drought (severity-duration and magnitude) showed that SPEI showed more intensities in shorter periods of time than SMDI, so it shows more magnitudes of drought. The investigation of the standardized vegetation cover index showed that in most of the sub-basins, since 2012, the decreasing trend of vegetation cover is evident. Investigating the relationship between SPEI and SMDI and SNDVI showed that SNDVI has a high correlation with SPEI and SMDI in a long-term time scale. A comparison of historical droughts between the three indices showed that, although all three indices often showed drought conditions, SPEI always showed extreme conditions compared to changes in soil moisture and vegetation, indicating a delayed response to changes in soil moisture. and vegetation to meteorological drought.